Pengaruh Myers Briggs Type Indicator (MBTI) Dengan Tingkat Stres Mahasiswa Kedokteran - Sari, Arine Talitha; Nawangsasi, Peppy; Irawati, Ade; Biutifasari, Verna (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2024)
Myers-Briggs Type Indicator (MBTI) is a tool to measure personality types whose results are presented through 4 dichotomies namely Extraversion/Introversion, Sensing/Intuition, Thinking/Feeling, and Judging/Perceiving. A person's personality type will affect the level of stress they feel. Stress is a condition when our body reacts due to a change in our environment, either physical or mental changes that cause us to feel disturbed. This study aims to determine the relationship between personality type based on Myers-Briggs Type Indicator (MBTI) with stress levels in medical students. This type of research is observational analytic. Respondents used were 62 people who were filled in by 2020 students at the Faculty of Medicine, Hang Tuah University and then analyzed using the Kendall Tau-b method. It was found that 15 respondents experienced mild stress, 39 respondents experienced moderate stress, and as many as 7 respondents experienced severe stress. 30 respondents of extroverted personality, 31 respondents of introverted personality, 43 respondents of sensing personality, 18 respondents of intuition personality, 28 respondents of thinking personality, 33 respondents of feeling personality, 52 respondents of judging personality and there are 9 respondents with perceiving personality type. The significance value between personality type and stress level exceeds the α value (α = 0.05) which means that there is no relationship between personality type and stress level